This preview shows pages 1–6. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Problem 81/82 A = { (3 , 1) , (3 , 2) , (3 , 3) , (3 , 4) , (3 , 5) , (3 , 6) } ,P ( A ) = 1 6 . B = { (1 , 4) , (2 , 4) , (3 , 4) , (4 , 4) , (5 , 4) , (6 , 4) } ,P ( B ) = 1 6 . C = { (1 , 6) , (2 , 5) , (3 , 4) , (4 , 3) , (5 , 2) , (6 , 1) } ,P ( C ) = 1 6 . P ( AB ) = P ( { (3 , 4) } ) = 1 36 . P ( AC ) = P ( { (3 , 4) } ) = 1 36 . P ( BC ) = P ( { (3 , 4) } ) = 1 36 . P ( ABC ) = P ( { (3 , 4) } ) = 1 36 . P ( AB ) = 1 36 = 1 6 1 6 = P ( A ) P ( B ) . P ( AC ) = 1 36 = 1 6 1 6 = P ( A ) P ( C ) . P ( BC ) = 1 36 = 1 6 1 6 = P ( B ) P ( C ) . P ( ABC ) = 1 36 6 = 1 6 1 6 1 6 = P ( A ) P ( B ) P ( C ) . Hence, the three events are pairwise independent, however, they are not (mutually) inde pendent. 1 Problem 83/104 Let R denote the need of rework. We have the following setup: P ( A 1 ) = 0 . 50 ,P ( A 2 ) = 0 . 30 ,P ( A 3 ) = 0 . 20 , P ( R  A 1 ) = 0 . 05 ,P ( R  A 2 ) = 0 . 08 ,P ( A 3  J ) = 0 , 069 . By the law of total probabilities: P ( R ) = P ( R  A 1 ) P ( A 1 ) + P ( R  A 2 ) P ( A 2 ) + P ( R  A 3 ) P ( A 3 ) = 0 . 069 . By Bayes rule: P ( A 1  R ) = P ( R  A 1 ) P ( A 1 ) P ( R ) = 0 . 362 . P ( A 2  R ) = P ( R  A 2 ) P ( A 2 ) P ( R ) = 0 . 348 . P ( A 3  R ) = P ( R  A 3 ) P ( A 3 ) P ( R ) = 0 . 290 . 2 Problem 99/24 (a) F ( x ) is a step function and thus X is a discrete rv. Furthermore, the jumps of F ( x ) occur at all the possible values of F ( x ), and the size of each jump is the probability of the possible value. Therefore the set of such values is { 1 , 3 , 4 , 5 , 12 } , and p X (1) = F (1) 0 = 0 . 30 . p X (3) = F (3) F (1) = 0 . 10 . p X (4) = F (4) F (3) = 0 . 05 . p X (6) = F (6) F (4) = 0 . 15 . p X (12) = F (12) F (6) = 0 . 40 . (b) P (3 X 6) = P ( X 6) P ( X < 3) = F (6) F (1) = 0 . 30 . P (4 X ) = 1 P ( X < 4) = 1 F (3) = 0 . 60 . 3 Problem 107/32 (a) E ( X ) = (13 . 5)(0 . 2) + (15 . 9)(0 . 5) + (19 . 1)(0 . 3) = 16 . 38 . E ( X 2 ) = (13 . 5) 2 (0 . 2) + (15 . 9) 2 (0 . 5) + (19 . 1) 2 (0 . 3) = 272 . 298 . V ( X ) = E ( X 2 ) [ E ( X )] 2 = 272 . 298 16 . 38 2 = 3 . 9936 . (b) E (25 X 8 . 5) = 25 E ( X ) 8 . 5 = 401 . (c) V (25 X 8 . 5) = 25 2 V ( X ) = 2496 . (d) E ( X . 01 X 2 ) = E ( X ) . 01 E ( X 2 ) = 13 . 657 . 4 Problem 107/36 Let pr be the (constant) premium that the company charges. Considering the deductible, the profit of the company is then computed as pr ( X 500) + , where ( X 500) + = ( X 500 , if X > 500 , , if X 500 ....
View Full
Document
 Summer '05
 STAFF

Click to edit the document details